2014
DOI: 10.1108/prog-08-2012-0048
|View full text |Cite
|
Sign up to set email alerts
|

The use of IT-based information services

Abstract: Purpose -The aim of this paper is to investigate the current status of public universities in Bangladesh in terms of library resources and services, IT infrastructure and training requirements for the establishment of a centralized, networked electronic library for the universities in the country. Design/methodology/approach -A survey was conducted in March-April 2012 to ascertain the level of library automation practices, access to online resources and IT facilities utilized by the public universities in Bang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The universities in Bangladesh lack adequate infrastructures, library resources, access to online databases and academic journals. Besides, many universities, especially those outsides of Dhaka, noticeably fail to have standard ICT facilities to access online resources (Ahmed, 2015). A recent study in a public university in Bangladesh found that many early career academics have an incorrect understanding of or are unfamiliar with many commonly used library terms such as reference, citation tools, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The universities in Bangladesh lack adequate infrastructures, library resources, access to online databases and academic journals. Besides, many universities, especially those outsides of Dhaka, noticeably fail to have standard ICT facilities to access online resources (Ahmed, 2015). A recent study in a public university in Bangladesh found that many early career academics have an incorrect understanding of or are unfamiliar with many commonly used library terms such as reference, citation tools, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The Government has initiated the digitization of libraries nationwide under the project of transforming traditional libraries into e-libraries, with the goal of ensuring smart access and service (UNB News, August 02, 2021). However, the practices of IT-based services in university libraries of Bangladesh are not satisfactory (Ahmed, 2014). Libraries of all sizes and types are now adopting emerging technology to meet the challenges of the fourth industrial revolution.…”
Section: Applications Ofmentioning
confidence: 99%
“…In this study, factors such as users' knowledge of the search domain, quality of digital library content, system characteristics, service quality, perceived ease of use, perceived usefulness and intention to use influenced digital library usage at East West University in Bangladesh. Ahmed (2014) aims to examine the current state of public universities in Bangladesh regarding their library resources, IT infrastructure and training needs for establishing a centralized electronic library network. The methodology involved conducting a survey among university librarians to gauge library automation practices, online resource access and IT facilities.…”
Section: Literature Reviewmentioning
confidence: 99%